Genetic Evidence for Causal Relationships Between Maternal Obesity-Related Traits and Birth Weight. Issue 7 (July 2016) - Tyrrell, Jessica; Richmond, Rebecca C.; Palmer, Tom M.; Feenstra, Bjarke; Rangarajan, Janani; Metrustry, Sarah; Cavadino, Alana; Paternoster, Lavinia; Armstrong, Loren L.; De Silva, N. Maneka G.; Wood, Andrew R.; Horikoshi, Momoko; et al.
Abstract : (Abstracted from JAMA 2016;315(11):1129–1140) Neonates born to overweight or obese women are more likely to be large for gestational age. It has been noted that maternal obesity-related traits are observationally associated with birth weight; however, the causal nature of these associations is uncertain.